Occurrences of corrosion: causes and prevention - Safiuddin, Md. (BRAC University, 2010)
Corrosion of metal is a ubiquitous phenomenon that occurs in various forms. Atmospheric or uniform, galvanic, crevice, pitting, and microbial corrosion are most familiar forms of corrosion. This note briefly demonstrates these five classes of corrosion with some practical examples. This note also discusses the rational causes of the five aforementioned forms of corrosion, and provides several preventive measures to protect the metals.